A modified rigid barrier for improved assessment of occupant injury in incompatible frontal collisions. (12th May 2009) - Deb, Anindya; Cheruvu, Kalyan S.; Ruan, Shi-jie
Recent statistics on road traffic fatalities indicate that occupants of low ride-height cars are generally at a disadvantage in frontal collisions against incompatible vehicles such as SUVs and pickup trucks. To overcome the inadequacy of current vehicle crash safety tests, it has been recently shown that a stepped rigid barrier (SRB) can be a cost-effective tool for assessing the safety performance of a unibody car in collision against a body-on-frame pickup truck. However, the potential of the SRB was shown in terms of its ability to better represent the severe upper body deformation a car can experience during collision against a pickup truck. It has been demonstrated here that new car assessment programme injury parameters also compare well in car-to-truck and car against the previously developed SRB collisions. The assessment of the SRB is done with the help of the explicit finite element analysis solver of LS-DYNA 960.